Single-Atom Iridium-Catalyst-Embedded Zeolitic Imidazolate Frameworks for CO2and Glycerol Transformations - Oh, Kyung Ryul; Yun, Gwang Nam; Kim, Ki Duk; Cheong, Yeon Joo; Yoo, Changho; Prihatno, Fajar; Jang, Hye Young; Valekar, Anil H.; Cha, Ga Young; Lee, Mijung; Jung, Jaehoon; Kwon, Young Uk; et al. (Chemistry of Materials, 2022)
Developing efficient immobilization techniques for organometallic complexes is essential for the fabrication of efficient single-atom catalysts (SACs) and the recycling of high-performance molecular catalysts. Here, we demonstrate facile methods for preparing SACs by incorporating an Ir complex into a zeolitic imidazolate framework (ZIF) support. The Ir(bis-carbene) complex was introduced at different stages of the ZIF-7-III synthesis, resulting in different immobilization efficiencies, particle shapes, and catalytic activities. The possible local structures were proposed by density functional theory modeling and compared with the X-ray absorption spectroscopy results, which established that the Ir(bis-carbene) moiety coordinates with the defective -N site of the benzimidazolate ligand. The prepared catalysts exhibited unprecedented turnover numbers (>30,000) for glycerol dehydrogenation and CO2 hydrogenation. Hot filtration and recycling tests confirmed the heterogeneity and stability of the catalyst under harsh reaction conditions. The findings of this study will promote the heterogenization of various organometallic complexes for diverse catalytic reactions.
Keywords: Bis-carbene; Facile method; Immobilization technique; Iridium catalyst; Molecular catalysts; Organometallic complex; Performance; Single-atoms; Zeolitic imidazolate frameworks; ]+ catalyst